Penerapan Model Pembelajaran Jigsaw untuk Peningkatan Kemampuan Menulis Teks Fabel pada Siswa SMP Negeri 3 Sanana - Buamona, Alfian; Gay, Masayu; Djais, Idwan (Peneliti.net, 2024)
The ability to write fable texts must be mastered by students in class VII of junior high school. However, this ability is still far from expectations for class VII students at SMP Negeri 3 Sanana. Therefore, efforts that can be made are to apply the jigsaw learning model through classroom action research with data collection techniques, namely tests, observations and interviews with 30 students. The t-test is used to determine the effect of using the jigsaw model accompanied by t-count and t-table. The results of data analysis show, firstly, that the writing ability of class VII students at SMP Negeri 3 Sanana, before using the jigsaw learning model, obtained a calculated average score (Pretest) of 34.1. Very low qualifications are in the value range (0-50). Second, the ability to write fable story texts for class VII students at SMP Negeri 3 Sanana after using the jigsaw learning model has a calculated average (Posttest) of 74.5. Qualifications Fair and good, sufficient is in the value range (61-70) and good is in the value range (71-80). Third, based on the results of the t-test, there is an influence on the use of the jigsaw model on the ability to write fable text for class VII students at SMP Negeri 3 Sanana, because T-count is greater > T-table (7.46 > 1,699).